Analysis of Solver Rule Construction Methods and Their Working Algorithms - U.U. Turapov (Zien Journals, 2022)
This article mainly analyzes the heuristic and statistical methods of building a decision rule, as well as their performance algorithms, and their advantages and disadvantages are extensively analyzed.
Keywords: heuristic; statistical; methods